UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA MELALUI METODE INDEX CARD MATCH SISWA KELAS VIIB SMP N 2 TEGALREJO KABUPATEN MAGELANG TAHUN AJARAN 2013/2014 - Nugroho Budi Santosa; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2014)
This study aims to describe the learning process of Index Card Match in order to increase the interest in mathematics and the learning outcomes of students of SMP N 2 â€œVIIBâ€ class Tegalrejo, Magelang regency, school year 2013/2014. Subjects in this study were â€œVIIBâ€, 2nd semester students of SMP N 2 Tegalrejo totaling 22 students. While the object of this study is the interest and the results obtained from the study of mathematics overall learning process on the application of the method Index Card Match. The results shows that the interest and learning of mathematics has increased. The average percentage of interest in learning from the results of the questionnaire pre-cycle is of 63.77 %. In the first cycle, the average poll percentage increases to 71.25 %. In the second cycle the average percentage interest in learning questionnaire increases to 80.71 %. Test results shows 9 students learn pre-cycle or 40.91 % of students have achieved KKM. In the first cycle achievement test, the students who achieved the KKM increases to 14 students or 63.64 %. In the second cycle also increases to 18 students or 81.82 % of students. Improved learning outcomes of students who achieve KKM pre-cycle until the second cycle, when accumulated by 40.91 % or 9 students.